The Effect Of Reinforcement On Writing Skill At Eleventh Grade Students In SMK Negeri 1 Pematang Siantar - Daniel Ganda Putra Sihombing; David Togi Hutahaean; Yanti kristina Sinaga; Tiarma Intan Marpaung; Anita Sitanggang (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The problem in this study is the lack of reinforcement, the lack of student writing skills. This study aims to determine The Effect Of Reinforcement On Writing Skill At Eleventh Grade Students In Smk Negeri 1 Pematang Siantar. The population in this study were eleventh grade OTKP students and the samples in this study were eleventh grade OTKP-2 students totaling 31 students. This type of research is non-experimental quantitative research, data collection techniques using a questionnaire expressed in the form of a Likert Scale and documentation. The test results show that (1) there is a significant influence between reinforcement on writing ability in eleventh grade students of OTKP SMK Negeri 1 Pematang Siantar obtained tcount>ttable of (3,082>2,045) with significance <0.05 (0.000<0.05), then in the determination test results obtained R Square of 0,24, this means that reinforcement (X1) is distributed by 24%, while the other 76% is explained by other variable not discussed in this study.